A conserved β‐bulge glycine residue facilitates folding and increases stability of the mouse α‐defensin cryptdin‐4. Issue 1 (26th November 2021) - Clark, Richard J.; Phan, Thanh Huyen; Song, Angela; Ouellette, André J.; Conibear, Anne C.; Rosengren, K. Johan
Abstract: Defensins are key components of both innate and adaptive immune responses to pathogens. Cryptdins are mouse alpha‐defensins that are secreted from Paneth cells in the small intestine and have disulfide‐stabilised structures and antibacterial activities against both Gram‐positive and Gram‐negative bacteria. The folding and three‐dimensional structures of alpha‐defensins are thought to depend on a conserved glycine residue that forms a β‐bulge. Here we investigated the role of this conserved glycine at position 19 of cryptdin‐4 (Crp4) in terms of the folding, structure and stability. A Crp4 variant with D‐Ala at position 19 folded efficiently, was stabilised by a large number of hydrogen bonds, and resisted proteolysis in simulated intestinal fluid. Although a variant with L‐Ala at position 19 was able to adopt the correct fold, it showed less efficient folding and was degraded more rapidly than the D‐Ala variant. These results demonstrate the key role that glycine residues can have in folding of bioactive peptides and can provide insights to guide design of stable antimicrobial peptides that fold efficiently. Abstract :